2018
DOI: 10.1051/m2an/2017030
|View full text |Cite
|
Sign up to set email alerts
|

On the homogenization of the Helmholtz problem with thin perforated walls of finite length

Abstract: In this work, we present a new solution representation for the Helmholtz transmission problem in a bounded domain in R 2 with a thin and periodic layer of finite length. The layer may consists of a periodic pertubation of the material coefficients or it is a wall modelled by boundary conditions with an periodic array of small perforations. We consider the periodicity in the layer as the small variable δ and the thickness of the layer to be at the same order. Moreover we assume the thin layer to terminate at re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 29 publications
1
19
0
Order By: Relevance
“…If the macroscopic part of the solution is extended in a smooth way to the endpoints, the extension is not necessarily regular, e.g. it may tend to infinity at the endpoints of the interface Γ [20,21]. A similar behaviour has been observed for the macroscopic solution for problems with oscillating boundaries with corners [28] or a domain with rounded corners [29].…”
Section: (D) Solution Representationsupporting
confidence: 52%
See 1 more Smart Citation
“…If the macroscopic part of the solution is extended in a smooth way to the endpoints, the extension is not necessarily regular, e.g. it may tend to infinity at the endpoints of the interface Γ [20,21]. A similar behaviour has been observed for the macroscopic solution for problems with oscillating boundaries with corners [28] or a domain with rounded corners [29].…”
Section: (D) Solution Representationsupporting
confidence: 52%
“…It has been proved in [21,Appendix B] that this problem is well posed and admits a unique solution in V ± (Ω ± ). It can then be shown that the leading part of this remainder towards infinity is the same as the leading part of the same problem written in the conical domain K ± instead of the domainΩ ± , i.e.…”
Section: (I) Inviscid Modelmentioning
confidence: 99%
“…The work [17] deals essentially with our setting. In [20], the authors are interested, in particular, in the end-points of the perforation. We recall at this point the loose interpretation of our result: We show that our effective equations (1.10) hold whenever a priori estimates are satisfied.…”
Section: Literaturementioning
confidence: 99%
“…Note that, in (3.1) the Dirichlet condition was chosen on all boundaries for ease of writing. This choice is however arbitrary and it does not affect the model, whose essential ingredients are the transmission conditions; in addition, the analysis does not apply near the ends of the array where a specific analysis is required, which is outside the scope of the present study [16]. In our simulations, Neumann boundary conditions on the lateral walls of the cavity avoid very small amplitudes within the cavity, which would fall within numerical errors.…”
Section: A Two-dimensional Cage In the Transient Regimementioning
confidence: 99%